Syntheses, Characterization and Biological Evaluation of a Series of 2-Phenylamino-5-(2-Chlorophenyl)-1,3,4-Oxadiazole Derivatives - Kumar, S; Srivastava, PK (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Electrochemical synthesis of 2-phenylamino-5-(2-chlorophenyl)-1,3,4-oxadiazoles have been carried out in good yields at platinum electrode through the electrochemical oxidation of acyl thiosemicarbazide at room temperature in acetic acid. Two platinum electrodes in the form of square plates were used as working as well as counter electrode and saturated calomel electrode was used as reference electrode. The structure of the compounds was confirmed by IR, NMR, mass spectral and elemental analyses. The antibacterial activity of the derivatives was also assessed and compared with data against a series of Gram-positive Klebsiella pneumoniae, Escherichia coli and Gramnegative bacteria Streptococcus aureus and Bascillus subtilis. The antifungal activity was assessed against the fungal strain Aspergillus niger, Crysosporium pannical, Pellicularia solmanicolor and Candida albicans and compared against the standard antifungal drug Griesvofulvin. Dhaka Univ. J. Pharm. Sci. 18(1): 75-83, 2019 (June)